La quitosana - Nakamatsu, Javier (2012)
Chitin is an abundant biopolymer that can be found in shells of crustaceans, insects and in squid and pota pen. Deacetylation of chitin produces chitosan, a more versatile polysaccharide due to its solubility and increased chemical reactivity. Chitosan is used in medicine, pharmaceutics, cosmetics, water treatment, agriculture and food industry.